Different findings in Tc-99m MDP bone scintigraphy of patients with sickle cell disease: report of three cases - Cerci, Sevirn S.; Suslu, Harun; Cerci, Celal; Yildiz, Mustafa; Ozbek, Feride M.; Balci, Tansel A.; Canatan, Duran (Japanese Society Nuclear Medicine, 2007)
Objective Sickle cell anemia is an inherited disorder caused by abnormal hemoglobin, the S hemoglobin. Although vaso-occlusive crises can occur virtually in any organ, they are particularly common in the bony skeleton of affected patients. Bone marrow necrosis, bone infarcts, osteomyelitis, and aseptic necrosis are common complications in patients with sickle cell disease. Beside these abnormalities of the skeletal system, diffuse micro or macro calcification resulting from both splenic infarction and repeated vaso-occlusive episodes in the kidneys can be shown by technetium-99m methylenediphosphonate (Tc-99m MDP) bone scintigraphy. We present here the different osseous and extraosseous abnormalities noted on bone scintigraphies of three patients with sickle cell anemia. Methods Whole-body bone scan was performed after injecting 740 MBq of Tc-99m MDP in three patients with sickle cell disease. Results Tc-99m MDP whole-body image of the first patient showed non-uniform uptake in the anterior and posterior aspects of multiple ribs and bilateral femurs and tibias that was attributed to repetitive infarcts. Additionally, increased activity in shoulders, right elbow, and right knee was consistent with arthritis. Tc-99m MDP image of the second patient demonstrated avascular necrosis of the left femoral head and diffuse activity in the enlarged kidneys. Increased activity in the spleen that was attributed to repetitive infarcts was visualized in bone scan of the third patient. Conclusions In light of the findings in these cases, bone scintigraphy is a reliable imaging method in detecting both osseous and extraosseous abnormalities of sickle cell disease and may be used initially.
Keywords: sickle cell disease; Tc-99m MDP bone scintigraphy; osseous; extraosseous abnormalities